Intelligent Modeling of Educational Curricula Based on Labor Market Vacancy Analysis Using Semantic and Generative AI - Pavliuk, Vitalii; Drevetskyi, Volodymyr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The article presents an intelligent system for modeling educational curricula based on labor market vacancy analysis using semantic and generative AI. The approach identifies key skills and competencies required by employers and transforms them into adaptive course structures. A semantic module extracts and clusters professional requirements, while a generative model synthesizes relevant learning content. The proposed solution demonstrates the potential to automatically align educational programs with real market demands, supporting data-driven curriculum design.